Evaluatıon Of Frıctıon Between Varıous Brackets And Arch Wıre Materıals - Yahya Tosun; Hanife Ünal (Galenos Yayinevi, 1998)
The aim of this study was to evaluate experimentally frictional forces produced between different brackets and arch wire materials. In the study, the frictional forces between four brackets (Stainless steel, porcelain, .polycarbonate and stainless steel friction free) and various arch wire materials were tested using a three dimensional friction testing apparatus. Friction increases as the wire size increases. FF bracket showed significantly lower frictional forces compared to all other brackets. Slippery NiTi wires whose surfaces were hardened by ion implanation method showed significantly low frictional values compared to SS, Co-Cr, NiTi and TMA wires. Twist flex also generated lower frictional resistances compared to NiTi, TMA and SS wires in all brackets. The frictional values obtained by SS brackets were higher than the others. The reason of this was the burrs on the slot of these brackets due to the manufacturing technique.